Investigation of an integrated hydrogen production system based on nuclear and renewable energy sources: a new approach for sustainable hydrogen production via copper-chlorine thermochemical cycles - Orhan, Mehmet Fatih (2011)
Hydrogen production via thermochemical water decomposition is a potential process for direct utilization of nuclear thermal energy to increase efficiency and thereby facilitate energy savings. Thermochemical water splitting with a copper–chlorine (Cu–Cl) cycle could be linked with nuclear and renewable energy sources to decompose water into its constituents, oxygen and hydrogen, through intermediate Cu and Cl compounds. In this study, we analyze a coupling of nuclear and renewable energy sources for hydrogen production by the Cu–Cl thermochemical cycle. Nuclear and renewable energy sources are reviewed to determine the most appropriate option for the Cu–Cl cycle. An environmental impact assessment is conducted and compared with conventional methods using fossil fuels and other options. The CO2 emissions for hydrogen production are negligibly small from renewables, 38 kg/kg H2 from coal, 27 kg/kg H2 from oil, and 18 kg/kg H2 from natural gas. Cost assessment studies of hydrogen production are presented for this integrated system and suggest that the cost of hydrogen production will decrease to $2.8/kg. Copyright © 2011 John Wiley & Sons, Ltd.